(untitled) (Journal of Nepal Physical Society, 2024)
Silicene has drawn enormous research interest due to its extraordinary properties and potential applications. It adopts sp3 hybridization in honeycomb structure and forms a buckled surface. We performed first-principles calculations to study the geometrical, electronic and stability related properties of silicene under the influence of uniaxial strain. Varying uniaxial strain, 0% to 8%, was applied along the x-direction of monolayer silicene to analyze its stability and reactivity under stress. Our results show the finite band gap in strained silicene instead of zero gap Dirac cone in pristine one. Furthermore, the adsorption energy of non-polar gas like methane is found to be higher in strained silicene comparing to that for unstrained silicene. This is relevant to store energy carrying gases (methane) at operating conditions.